Chemical signals and social structures strengthen sexual isolation in Drosophila pseudoobscura - Jacob A. Jezovit; Joel D. Levine (Communications Biology)
Abstract Species that coexist in hybrid zones sexually isolate through reproductive character displacement, a mechanism that favours divergence between species. In Drosophila, behavioural and physiological traits discourage heterospecific mating between species. Recently, social network analysis revealed flies produce strain-specific and species-specific social structures. A gene, degrees of kevin bacon (dokb) has also been discovered that accounts for differences in social structures between flies. Why differences in social structures exist between drosophilids is currently unknown. Here we show through an experimental evolution study that six generations of selection in experimental sympatry led to the divergence of social structures measured in Drosophila pseudoobscura and Drosophila persimilis flies. We found that the frequency of hybrid offspring decreased within a few generations, suggesting social structures are associated with the sexual isolation of species. We also report increased species’ differences in the concentration of the cuticular hydrocarbon 5, 9-pentacosadiene after six generations of selection. The mean concentration of this compound converged in female flies of both species and diverged in male flies of both species, suggesting a quantitative link between increased sexual dimorphism and sexual isolation. Our results suggest that chemical signals, together with social structures, increase the sexual isolation between species in hybrid zones.